How to train practising gynaecologists in total laparoscopic hysterectomy: protocol for the stepped-wedge IMAGINE trial. Issue 5 (9th May 2019) - Obermair, Andreas; Armfield, Nigel R; Graves, Nicholas; Gebski, Val; Hanna, George B; Coleman, Mark G; Hughes, Anne; Janda, Monika
Abstract : Introduction: Hysterectomy is the most common major gynaecological procedure in women and minimally invasive approaches should be used wherever possible; total laparoscopic hysterectomy (TLH) is one such surgical approach which allows removal of the uterus entirely laparoscopically. However, lack of surgical training opportunities is impeding its increased adoption. This study will formally test a surgical outreach training model to equip surgeons with the skills to provide TLH as an alternative to total abdominal hysterectomy (TAH). Methods and analysis: Stepped wedge implementation trial of a surgical training programme for practising obstetrician gynaecologist specialists in four hospitals. Primary outcomes: Change in the proportion of hysterectomies performed by TAH, measured between preintervention and postintervention; we aim to reduce TAH by at least 30% in 75% of the trainees. Secondary outcomes: (1) Number of hospitals screened, eligible, agree to training and complete the training; (2) number of surgeons screened for eligibility, eligible, agree to training, who complete training and achieve proficiency; (3) proportion of trainees achieving proficiency in correct theatre setup, vascular exposure, mobilisation and surgery closure; change in proportion proficient over time; (4) adverse events (conversion from TLH to TAH, anaesthetic incident, intraoperative visceral injury, red cell transfusions, hospital stay >7 days, incidental finding of malignancy, unplanned readmission, admission to intensive care, return to theatre, postoperative pulmonary embolism or deep vein thrombosis, development of a fistula, vault haematoma, vaginal vault dehiscence or pelvic infection); (5) hospital length-of-stay; (6) cost-effectiveness and (7) trainee surgeon proficiency with TLH. Ethics and dissemination: The study has been approved by the Royal Brisbane and Women's Hospital Human Research Ethics Committee and has received site-specific approval from all participating hospitals. Results will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT03617354 ; Pre-results.